Heavier Alkali‐metal Gallates as Platforms for Accessing Functionalized Abnormal NHC Carbene‐Gallium Complexes. Issue 22 (28th September 2016) - Uzelac, Marina; Kennedy, Alan R.; Hernán‐Gómez, Alberto; Fuentes, M. Ángeles; Hevia, Eva
Abstract : By sequentially treating the unsaturated carbene IPr [IPr = 1, 3‐bis(2, 6‐diisopropylphenyl)imidazol‐2‐ylidene] with heavier alkali‐metal alkyls Na R or K R ( R = CH2 SiMe3 ) and Ga R 3, novel heteroleptic gallates1 and2 were prepared. Incorporating anionic NHC ligands, these bimetallic complexes react selectively with electrophilles to afford neutral abnormal NHC Ga complexes under mild conditions. Abstract :